Loss of PKBβ/Akt2 predisposes mice to ovarian cyst formation and increases the severity of polycystic ovary formation in vivo - David F. Restuccia; Debby Hynx; Brian A. Hemmings (The Company of Biologists, 2012)
SUMMARY Ovarian cysts affect women of all ages and decrease fertility. In particular, polycystic ovarian syndrome (PCOS), in which multiple follicular cysts develop, affects 5-10% of women of reproductive age and can result in infertility. Current non-invasive treatments for PCOS can resolve cysts and restore fertility, but unresponsive patients must undergo severe ovarian wedge resection and resort to in vitro fertilization. PCOS is related to the deregulation of leutinizing hormone (LH) signaling at various levels of the hypothalamic-pituitary-ovarian axis and resultant hyperproduction of androgens. Because insulin resistance and compensatory hyperinsulinemia are observed in 50-70% of individuals with PCOS, deregulated insulin signaling in the ovary is considered an important factor in the disease. Here we report that aged mice specifically lacking the PKBβ (also known as Akt2) isoform that is crucial for insulin signaling develop increased testosterone levels and ovarian cysts, both of which are also observed in insulin-resistant PCOS patients. Young PKBβ knockout mice were used to model PCOS by treatment with LH and exhibited a cyst area that was threefold greater than in controls, but without hyperinsulinemia. Thus, loss of PKBβ might predispose mice to ovarian cysts independently of hyperactive insulin signaling. Targeted therapeutic augmentation of specific PKBβ signaling could therefore provide a new avenue for the treatment and management of ovarian cysts.